I psifidoti girlanda tou troullou tis Agias Sofias Thessalonikis - CHEIMONOPOULOU, M. (Thessalonikeon Polis, 2007)
The paper examines the garland that frames the Ascension of Christ in the dome mosaic of Saint Sophia inThessaloniki with short references to examples of garlands and wreaths in floor and wall mosaics from Hellenistic to Late Byzantine Era. The garland found in the mosaics of Saint Sophia in Istanbul is very similar. As regards the garland of Saint Sophia in Thessaloniki, the author claims that, in the context of the Ascension of Christ, it is used as a victory symbol, emphasizes the historical fact of the Ascension and thus underlines its eschatological meaning.
p. 14-23, 11 ill. n.b. et coul.
Keywords: Iconographie; Ascension (scène biblique); Byzance, byzantin (art, civilisation); Christ; Dôme; Église (Thessalonique, GRC) Sainte-Sophie; Eschatologie, eschatologique; Guirlande; Mosaïque [de voûte]; Mosaïque [pariétale]; Symbole, symbolisme; Victoire (symbole de); Grèce; Thessalonique